The Effect of Sweet Taste on Romantic Semantic Processing: An ERP Study - Wang, Liusheng; Chen, Qian; Chen, Yan; Zhong, Ruitao (Frontiers in Psychology, 2019)
Previous studies have found that sweet perception affects the subjective evaluation of interpersonal intimacy and romantic semantic processing. However, the cognitive processes involved in this effect are unclear. The aim of the current study was to investigate the sweet-love embodied effect in semantic processing and its underlying mechanism by Event-Related potentials technique. Participants were randomly exposed to sweet-taste or tasteless conditions, during which they performed a lexical decision-task that involved romantic and non-romantic words. The results showed an enhanced N400 for romantic words compared to non-romantic words in the sweet-taste condition, and a larger P200 for romantic words relative to non-romantic words. The results demonstrate that taste sensations can cross-modally facilitate the semantic processing of romance. These findings support the embodied effect of sweet-love and are discussed from the perspective of embodied cognition with knowledge activation of concept and semantic richness.